Socio-economic condition and mental anxieties among empty-nest rural elderly - Karamat Ali; Md. Siddiqur Rahman; Ety Rani (Universitas Airlangga, 2022)
The number of empty-nest elderly is increasing day by day. They are facing different kinds of problems. In this study, efforts have been made to investigate the socio-economic condition and mental anxieties among the empty-nest rural elderly. The method used in this research was the quantitative approach, using a survey and questionnaire methods. Data have been collected from 32 empty-nest elderly both males and females aged 60 and above. In this study, researchers have selected three villages in Shailkupa Upazila under the district of Jhenaidah in the division of Khulna, Bangladesh. Three villages are- Ananto Badalsho, Badalsho, and Aushia. Data were collected using informed consent from June 14, 2017 to June 29, 2017. In this study, the highest of the respondents’ socio-economic conditions are satisfactory. All of the respondents feel lonely. A majority of the respondents suffer from mental anxieties. The main causes of their mental anxieties are their children live far from them and they have serious health problems. Since their children live so far from them, their children cannot look after them during their illness. This time they depend on either neighbors or others.